De borregos enjeitados a bichos miúdos: ilustrações da infância do romance brasileiro de 30 - Timbó, Margarida Pontes (2016)
In this work I intend to mark the presence of childhood and family notions in four novels from the 30’s Romance in the Northeast. They are: A Bagaceira (1928), by José Américo de Almeida; O Quinze (1930), by Rachel de Queiroz; Menino de Engenho (1932), José Lins do Rego; Vidas Secas (1938), by Graciliano Ramos. The work is projected through a reading of childish images, focusing on the character’s relationship (or the narrator’s when he reports his childhood) with his family. It itends to be another way of inflexion, adding a new way of reading in respect to the interpretation of the referred novels, which are looked most of time through the view of the telluric literature, and that of social function, including the par textual apparatus, They are represented by the illustrations in the covers of the books, which embodies different periods and editorial publications. The 30’s was really fructifull to the Brazilian Art and Literature, and the first artistic illustrations printed in the covers of the novel’s editions appear in this period. The inner illustrations appear in post editions, specifically from the 6th one on. As the covers and illustrations are iconic ‘manifestations’ that work as par text (GENETTE, 2009), they also use the inner illustrations created by the artists Candido Portinari, Aldemir Martins e Poty Lazarotto as corpus. The theoretical and bibliographical research is based on the reading of the critical fortune of the novels, according to Bueno (2006), Castello (1961a), (1961b), Montello (1983), among others. She is also in accordance with Genette (2009), Lima (1985), Linden (2011), Nikolajeva e Scott (2011). These workers who study the illustration and its relation with the literary text, and, finally, is based on Ariès (2006), Badinter (1985), Coutinho (2012a), (2012b), Corazza (2004) and others who study relative themes to the childhood, and to the family. I intend to verify that, starting from sociological readings, it is possible to investigate the child character’s through the idea of abandonment. This abandonment, however, should not be undersrtood as a consequence of the nature’s hardness in the descripted spaces in the romance experiences, nor the consequence of the coldness that starts to spread in the nuclear family. I examine in two novels the presence of a orphanage, in other, the abandonment is the same. I examine in two novels the presence of the orphanage, and in another, the maternal abandonment, that’s it, diferente factors that define the quality of the protagonists’ existence, to the ones is aplicable very appropriately the sintagma: “borrego enjeitado”, which also can be read the works’ inner illustration. To the prottagonists it is applicable the sintagma: ‘bichos miúdos’, which regards to the way the child characters live singular experiences with the neighboor, especially with his mother. So, illustrations question these experiences among family. I hope that as soon as this study can, it assumes the importance of the child in the written text, showing the way the illustrations can rewrite the ficcion, and the figurine of the characters.